Karya al-Tawabi’ wa al-Zawabi’ oleh Ibn Shuhayd (382-426H) dan Risalat al-Ghufran oleh al-Ma’arri (363-449H): Satu Adaptasi daripada Peristiwa Isra’ Mi’raj - Mohd Shahrizal, Nasir
Fourteen hundred years ago al-Isra‟ wa al-Mi„raj or „The Night Journey‟ brought to the world something that changed the course of history. The Isra‟ Mi„raj is considered a sign of Allah‟s power by the God conscious. Therefore, this magnificent journeywhich contains a thousand and one wisdoms and miracles is very significant in Islam and will remain etched in the history of Islam. This article discusses the impact of the Isra‟ Mi„rajin the world of Arabic literature. For this purpose, this study will analysestwo examples ofArabic literary works, which have been directly or indirectly inspired by the Isra‟ Mi„raj: al-Tawabi„wa al-Zawabi„andRisalatal-Ghufran. This articleunveils a number of issues, which are seen as a direct result from the impact of the Isra‟ Mi„raj. Should this aspect really exist in these literary works, an inevitable fact avails, which is, that the Isra‟ Mi„rajhas definitely played a significant role in fiction writings of Arabic literatures. Having established the above, caution should be practiced to ensure that the truth behind the Isra‟ Mi„rajbe preserved and protected from any negative and offensive elements towards Islam and Muslims, notwithstanding the artistic nature of the works in scrutiny.Without any doubt, Isra‟ Mi„raj is a fact that has been mentioned in the Qur‟an and the authentic Hadithof the Prophet Muhammad SAW